2013
DOI: 10.1177/000313481307901033
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Advanced Adrenocortical Carcinoma: A 21-year Population-based Analysis

Abstract: Adrenocortical carcinoma (ACC) is a rare endocrine malignancy with a dismal prognosis. When diagnosed in advanced stages of the disease, the outcomes of surgical resection are not well understood. The objective of this study is to determine the impact of surgery in patients with advanced ACC. Using the Surveillance, Epidemiology and End Results database, we identified patients diagnosed with Stage III and IVACC between 1988 and 2009. A total of 320 patients with Stage III and IV disease were included in our an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 15 publications
5
38
1
5
Order By: Relevance
“…Adverse effects from chemotherapy, however, are common and diverse (see Appendix 6). Sixteen studies focused on surgery in recurrent and advanced ACC; six publications reported on oligometastasectomy (lung and liver) (126,127,128,129,130,131), whereas ten publications assessed the effect of surgery in local recurrent and/or metastatic disease (61,66,78,132,133,134,135,136,137,138). In patients with metastasectomy, 5-year survival rates up to 40% were reported (126,127), although control groups were lacking (+OOO).…”
Section: Question 4: Therapy For Advanced or Recurrent Diseasementioning
confidence: 99%
“…Adverse effects from chemotherapy, however, are common and diverse (see Appendix 6). Sixteen studies focused on surgery in recurrent and advanced ACC; six publications reported on oligometastasectomy (lung and liver) (126,127,128,129,130,131), whereas ten publications assessed the effect of surgery in local recurrent and/or metastatic disease (61,66,78,132,133,134,135,136,137,138). In patients with metastasectomy, 5-year survival rates up to 40% were reported (126,127), although control groups were lacking (+OOO).…”
Section: Question 4: Therapy For Advanced or Recurrent Diseasementioning
confidence: 99%
“…5,[12][13][14][15] Among these studies, reported rates of lymphadenectomy range from only 6% to 33%. 3,5,[12][13][14][15][16][17] Moreover, examination of any lymph nodes has been alarmingly low, with reported rates less than 35%. 3,5,[12][13][14][15][16][17] Despite the low frequency of lymph node examination, nodal metastasis has been identified as an independent negative predictor of survival.…”
Section: Introductionmentioning
confidence: 99%
“…When discovered, surgery remains the only possible curative treatment for patients with ACC . Despite several studies suggesting an improved survival over the last 20 years, the prognosis of patients after surgical resection is not well defined with overall 5‐year survival ranging widely from 16% to 77% . Currently, the most commonly utilized scheme to predict prognosis for patients with ACC is the AJCC tumor, node, metastasis (TNM) staging system .…”
Section: Introductionmentioning
confidence: 99%
“…While several tumor specific morphologic factors have been associated with prognosis (e.g., tumor size), other prognostic factors are not well defined, largely because of the small sample size of most studies . Several studies have examined prognostic factors including patient‐ and tumor‐specific characteristics, but the impact of other constitutional factors such as the immune system have not been investigated among patients with ACC .…”
Section: Introductionmentioning
confidence: 99%